Are glomerular filtration rate estimations necessary before high dose methotrexate?. Issue 4 (1st October 1999) - Rees, H; Hann, I M; Chessells, J M; Webb, D K H
Abstract : Glomerular filtration rates (GFR) were estimated in 168 children (227 estimates) before treatment for haematological malignancies with high dose, intravenous methotrexate. Clinical management was altered on the basis of GFR in only two cases, both of whom had tumour lysis syndrome. Routine estimations of GFR do not contribute to management.